2012
DOI: 10.1039/c1cp22876e
|View full text |Cite
|
Sign up to set email alerts
|

Increasing visible-light absorption for photocatalysis with black BiOCl

Abstract: Black BiOCl with oxygen vacancies was prepared by UV light irradiation with Ar blowing. The as-prepared black BiOCl sample showed 20 times higher visible light photocatalytic activity than white BiOCl for RhB degradation. The trapping experiment showed that the superoxide radical (O(2)(•-)) and holes (h(+)) were the main active species in aqueous solution under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
229
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(246 citation statements)
references
References 36 publications
17
229
0
Order By: Relevance
“…Nitroblue tetrazolium chloride (NBT, 2.5 × 10 − 5 mol/L, exhibiting an absorption maximum at 259 nm) was used to determine the amount of O 2 U− generated in the BiOBr and BiOCl photocatalytic systems (Ye et al, 2012a). The production of O 2 U− was quantitatively analyzed by detecting the absorption decrease of NBT.…”
Section: Active Species Analysismentioning
confidence: 99%
“…Nitroblue tetrazolium chloride (NBT, 2.5 × 10 − 5 mol/L, exhibiting an absorption maximum at 259 nm) was used to determine the amount of O 2 U− generated in the BiOBr and BiOCl photocatalytic systems (Ye et al, 2012a). The production of O 2 U− was quantitatively analyzed by detecting the absorption decrease of NBT.…”
Section: Active Species Analysismentioning
confidence: 99%
“…As investigated, the oxygen vacancies can not only serve as photoinduced charge traps to prevent the electron−hole recombination, they are also effective adsorption sites to adsorb active species which may greatly increase the photocatalytic activity 17,18 . Moreover, oxygen vacancies can also form oxygen vacancy states lying close to the conduction band of the photocatalyst, which can enhance its visible light response 17 . Except for TiO 2 and BiOCl, Zhu et al 18,19 also reported that oxygen vacancies enriched BiPO 4 nanorod, prepared by vacuum deoxidation, showed enhanced photocatalytic activity and expanded photocatalytic response (more than 365 nm).…”
Section: Introductionmentioning
confidence: 99%
“…However, the charge separation in this p-n heterojunctions always undergoes the photogenerated electrons transferring to the CB of BiPO 4 leaving holes on the VB of narrow band semiconductors [12][13][14] , which can hardly use the high oxidation ability of holes in the higher VB of BiPO 4 . Recently, the oxygen defects have been reported can greatly enhance the photocatalytic activity and expand the range of photoresponse in the semiconductor photocatalysts [15][16][17][18] . As investigated, the oxygen vacancies can not only serve as photoinduced charge traps to prevent the electron−hole recombination, they are also effective adsorption sites to adsorb active species which may greatly increase the photocatalytic activity 17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] But for photocatalytic systems, the high rate of electron-hole recombination is due to the high band gap (3.4 eV).…”
Section: Introductionmentioning
confidence: 99%